FREQUENCY OF EXTERNAL HERNIAS IN AYUB TEACHING HOSPITAL ABBOTTABAD - Sultan, Babar; Quresh, Zaheeruddin; Malik, Masud Akhtar (Journal of Ayub Medical College Abbottabad, 2009)
Background: Hernia is a protrusion of a viscous or a part of a viscous through an abnormal opening in wall of its containing cavity. Different external hernias present differently and ultimate treatment is surgical, which is most commonly performed elective operation in the world. The objectives were to know the age and gender wise frequency of external hernias in Ayub Teaching Hospital, Abbottabad. This retrospective study was conducted at the surgical units of Ayub Teaching Hospital from June 2004 to June 2005. Methods: Records of all cases of hernias operated in Ayub Teaching Hospital during June 2004 to June 2005 were retrieved from the operation registers of the entire three surgical units available at the operation theatres. The data was collected on a proforma and was analysed by SPSS-16. Results: Of the 1063 cases, 982 (92.38%) were male and 81 (7.62%) were female. Right Inguinal Hernia (RIH) was the most frequent as expected, i.e., 44.12%, followed by Left Inguinal Hernias (LIH) 18.72%. Least common hernias were femoral hernias with a frequency of 0.85%. Conclusion: It is concluded that 85% hernias occur in the groin, with 12% incisional and only 3% hernias occur elsewhere. To reduce the rate of complications, health education is the most important intervention. For future health planning maintenance of disease register can not be over emphasised. Keyword: External Hernias, Deep inguinal rings, Inguinal ligamnents, Umbilical ring.